Criticism and Study of Mohammed Aladdin Mansour’s Translation of Ismail Fasih’s Novel Titled: Winter of 84 - Abdulhadi, Rafal Muwaffaq (Al-Adab Journal, 2020)
Translation has an important role in the transmission of information , exchanging culture and literature among nations, notably the translation of literary texts which have features and characteristics. However, translation faces some difficulties too. The translator of literary texts should have special competencies that result in deep and accurate understanding of the source text and the adequate command of the target language in order to translate the meaning of literary texts and their concepts.In this paper mistranslation samples in the Arabic translation by Mohammed Aladdin Mansour for Ismail Fasih’s Novel Titled (Winter 84) were studied and criticized . An attempt has been made in this paper to examine the defects and mistakes that occurred in this novel pointing out the importance of this novel and its standing among modern Persian novels in terms of the time period in which it was written, that is the eighties of the past century in which the Iranian -Iraqi war cast its shadows and reflections on the southern Iranian society in particular where the novels events took place. Since the translation of this novel has mistakes that cannot be ignored the researcher has made it an example to study the problems and challenges of translation between Arabic and Persian in our present time.